2016
DOI: 10.26740/jaj.v8n1.p1-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Green Accounting To Support Corporate Social Responsibility (Case Study : Semen Gresik Hospital)

Abstract: The Implementation of green accounting in hospital activities is the first step to solved environmental problems. Implementation of green accounting will work up the ability to minimize the environmental problem. The purpose of this accounting process is to improve the efficiency of environmental management by assessing environmental activities from a cost point of view (environmental cost). This research is a descriptive qualitative study using case studies method on Semen Gresik Hospital. This study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
1
9
0
2
Order By: Relevance
“…Based on the results of hypothesis testing conducted, it is known that the implementations of recycled materials, renewable energy, and green cost allocation have a positive effect on improving environmental performance mining and energy companies in Indonesia. This result is in accordance with Marota (2017), Hendratno (2016), and Khoirina (2016. This result is also consistent with the legitimacy theory.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results of hypothesis testing conducted, it is known that the implementations of recycled materials, renewable energy, and green cost allocation have a positive effect on improving environmental performance mining and energy companies in Indonesia. This result is in accordance with Marota (2017), Hendratno (2016), and Khoirina (2016. This result is also consistent with the legitimacy theory.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, complete and accurate environmental information will produce good environmental performance (Deswanto & Siregar, 2018). The results of Khoirina (2016) and Khoiruman and Haryanto (2017) explained that disclosure of environmental costs to management had a positive effect on environmental performance. The results of similar studies were also found related to the application of green accounting to improving environmental performance (Hendratno, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The application of environmental cost accounting aims to find out how much environmental costs are incurred in managing the waste by using an accounting system so that it can minimize the costs incurred and can control the company's responsibility in protecting the surrounding environment. (Ibrahim & Souleiman, 2018;Khoirina, 2016). Environmental cost accounting needs to be reported separately based on the cost classification.…”
Section: Environmental Cost Accounting Based On a Amanah Metaphor To ...mentioning
confidence: 99%
“…Hospitals as health organizations are expected to be responsible, to prevent or reduce the impact of bad things that can cause damage to the environment and the community around the hospital (Khoirina, 2016). As a form of hospital responsibility, it is hoped that there will be accounting treatment for company waste management (Trisnawati, 2014;Islamey, 2016), and what is considered more appropriate to use is green accounting, because it is more fundamental and has ecological nuances (Gallhofer and Haslam, 1997;Greenham , 2010;Thornton, 2013) which is based on the theory of three basic pillars of corporate responsibility Elkington (1997Elkington ( , 2001 namely economic responsibility (profit), social responsibility (people), and environmental responsibility (planet) (Lako, 2018;and Wibisono, 2007), so that the application of green accounting in hospitals will be based on financial, social and environmental activities (Ashari, et.al., 2020).…”
Section: Introductionmentioning
confidence: 99%